Translations and rotations are correlated in granular gases - Brilliantov, Nikolai V.; Pöschel, Thorsten; Kranz, W. T.; Zippelius, A. (Physical Review Letters, 2007)
In a granular gas of rough particles the axis of rotation is shown to be correlated with the translational velocity of the particles. The average relative orientation of angular and linear velocities depends on the parameters which characterize the dissipative nature of the collision. We derive a simple theory for these correlations and validate it with numerical simulations for a wide range of coefficients of normal and tangential restitution. The limit of smooth spheres is shown to be singular: even an arbitrarily small roughness of the particles gives rise to orientational correlations. © 2007 The American Physical Society.